Building an Evaluation Instrument for China's Hospital Emergency Preparedness: A Systematic Review of Preparedness Instruments. (13th March 2014) - Tang, Rong; Fitzgerald, Gerard; Hou, Xiang-Yu; Wu, Yang-Ping
Abstract: Objectives: The aim of this report is to identify from the literature common themes relating to the concept of hospital preparedness for emergencies to develop an agreed framework for evaluation. Method: A systematic literature search identified appropriate articles for critical appraisal. A meta-ethnography approach was used to synthesize the findings, using both reciprocal translation and line-of-argument synthesis. Results: From an initial 2162 articles, we identified 13 articles that specifically addressed the aims of this review and formed the basis of the intended analysis. Conclusion: Hospital emergency preparedness is essential for effective disaster relief. Developing a systematic and structured methodology is necessary to assess hospital preparedness. ( Disaster Med Public Health Preparedness : 2014:0:1-9)